2011
DOI: 10.1128/jvi.02050-10
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Differentially Modulates the Unfolded Protein Response To Facilitate Replication and Immune Evasion

Abstract: For intracellular survival it is imperative that viruses have the capacity to manipulate various cellular responses, including metabolic and biosynthetic pathways. The unfolded protein response (UPR) is induced by various external and internal stimuli, including the accumulation of misfolded proteins in the endoplasmic reticulum (ER). Our previous studies have indicated that the replication and assembly of the flavivirus West Nile virus strain Kunjin virus (WNV KUN ) is intimately associated with the ER. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
204
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(214 citation statements)
references
References 57 publications
(65 reference statements)
9
204
1
Order By: Relevance
“…In addition to PERK, eIF2a can be phosphorylated by a number of other kinases, including PKR, which recognizes (viral) dsRNA (Harding et al, 2002). To allow the translation of viral proteins, most viruses prevent the phosphorylation of eIF2a (Ambrose & Mackenzie, 2011;Burnett et al, 2012;Groskreutz et al, 2010). Although inhibition of eIF2a phosphorylation via CHIKV nsP4 has been reported (Rathore et al, 2013), we and others have found that alphaviruses are exceptional in allowing the phosphorylation of eIF2a during productive infection (Gorchakov et al, 2004;Nivitchanyong et al, 2009;Ventoso et al, 2006;White et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to PERK, eIF2a can be phosphorylated by a number of other kinases, including PKR, which recognizes (viral) dsRNA (Harding et al, 2002). To allow the translation of viral proteins, most viruses prevent the phosphorylation of eIF2a (Ambrose & Mackenzie, 2011;Burnett et al, 2012;Groskreutz et al, 2010). Although inhibition of eIF2a phosphorylation via CHIKV nsP4 has been reported (Rathore et al, 2013), we and others have found that alphaviruses are exceptional in allowing the phosphorylation of eIF2a during productive infection (Gorchakov et al, 2004;Nivitchanyong et al, 2009;Ventoso et al, 2006;White et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The IRE1a-XBP1 arm of the UPR has been shown to be activated during infection with other viruses (Ambrose & Mackenzie, 2011;Barry et al, 2010;Isler et al, 2005). To investigate whether CHIKV infection induced XBP1 mRNA splicing, Vero cells were mock infected, infected with CHIKV or treated with TM in a time-course experiment.…”
Section: Effect Of Chikv Infection On Upr Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, membrane remodelling can also improve viral multiplication by hiding viral components from the innate immune system [1, 12,86]. In flaviviruses (DENV and WNV) the evasion of interferon response has been shown to depend on the expression of hydrophobic viral proteins involved in membrane rearrangements [87][88][89]; in particular, the cholesterol content of these membranes is important to down regulate the interferon-stimulated antiviral signalling response to infection [90]. Related to this, antiviral interferon response also involves down regulation of sterol biosynthesis [91].…”
Section: Cellular Membranes and Viral Replication Complex Assemblymentioning
confidence: 99%